2017
DOI: 10.15835/buasvmcn-fst:12634
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of essential oils extracted from different aromatic plants by FTIR spectroscopy

Abstract: Four essential oils isolated from dried leaves of parsley, lovage, basil and thyme were investigated by FTIR spectroscopy. The analysis of recorded spectra revealed that the main compounds of tested essential oils dominate their vibrational spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…The C=C-C stretching vibrations are manifested at 1516 and 1589 cm −1 . The C-H vibrational groups coupled in different chemical configurations present specific IR bands in 2800-3400 cm -1 and 700-1500 cm −1 spectral ranges (see Table 3) [31][32][33][34][35]. The antioxidant and antibacterial properties of A. absinthium L. essential oil and extracts and the antimicrobial mechanisms involved, were reported in several papers.…”
Section: Resultsmentioning
confidence: 99%
“…The C=C-C stretching vibrations are manifested at 1516 and 1589 cm −1 . The C-H vibrational groups coupled in different chemical configurations present specific IR bands in 2800-3400 cm -1 and 700-1500 cm −1 spectral ranges (see Table 3) [31][32][33][34][35]. The antioxidant and antibacterial properties of A. absinthium L. essential oil and extracts and the antimicrobial mechanisms involved, were reported in several papers.…”
Section: Resultsmentioning
confidence: 99%
“…In the spectrum of the HAp-P from Figure 3b, IR bands characteristic of P-EO can be identified (marked in Figure 3c). In the spectral regions of 400–1000 and 1000–1200 cm −1 , the overlapping of P-EO and HAp IR bands determined the formation of the broad molecular bands observed in Figure 3b [47,48,49,50,51]. Finally, it should be noted that the absorption bands at 917, 1283, 2430, 3320, 3487, 3561, and 3581 that distinguish the formation of octacalcium phosphate are not observed in the HAp and HAp-P spectra, and certify the HAp stoichiometry (Ca/P ratio = 1.67).…”
Section: Resultsmentioning
confidence: 99%
“…Essential oils are among the active agents used to enhance the functionality of edible films. It is well known essential oils possess antioxidant, antibacterial, and antifungal properties and that their chemical compounds are responsible for these [ 1 , 4 , 5 ]. Several studies have reported that essential oil of tarragon exhibits antioxidant activity [ 6 , 7 , 8 , 9 ] and is efficient against various food-related microorganisms such as Bacillus subtilis [ 10 ], Escherichia coli [ 7 , 10 ], Pseudomonas aeruginosa [ 10 ], Staphylococcus aureus [ 7 , 8 , 10 ], Listeria monocytogenes [ 8 ], Proteus vulgaris [ 10 ], Alcaligenes faecalis [ 8 ], Shigella dysenteriae [ 8 ], Aerobacter aerogenes [ 10 ], Candida albicans [ 7 , 11 ], Saccharomyces cerevisiae var.…”
Section: Introductionmentioning
confidence: 99%